Cloud object storage as a service : IBM Cloud Object Storage from theory to practice - Patil, Anil (IBM redbooks., 2017)
For solution developers, architects, and IT specialists who are implementing Cloud Object Storage solutions, this IBM Redbooks publication focuses on the IBM COS public offering, IBM COS Public Services, and hybrid solutions leveraging this offering. --